Verizon rethinking Enterprise Network (Telecomworldwire, 2015)
The digital transformation and its impact on networks is the subject of a first-of-its kind report from [Verizon] called "Digital Transformation Powers Your Business." More than two-thirds (67 percent) of IT leaders surveyed for the report told Verizon that legacy networks can be a bottleneck to success. Nearly 80 percent of them said that it was IT's responsibility to ensure the network can support a company's digital transformation plans, and a vast majority of respondents said that the network is integral to the competitive advantage of a connected business. Verizon commissioned Forrester Research to study attitudes toward business challenges and transformation. The research took place in February 2015, and more than 600 decision makers at large enterprises and multinational corporations took part. Respondents came from North America, Latin America, EMEA and Asia Pacific.